Continuous wave and pulse (2–100 ns) high power AlGaAs/GaAs laser diodes (1050 nm) based on high and low reflective 13th order DBR. (29th November 2019) - Zolotarev, V V; Leshko, A Yu; Shamakhov, V V; Nikolaev, D N; Golovin, V S; Slipchenko, S O; Pikhtin, N A
Abstract: The paper presents the experimental results of a study of higfh-power laser diodes with a surface distributed Bragg reflector of 13-th and 16-th diffraction order emitting at a wavelength of 1026 nm and 1050 nm in a continuous and pulsed pump mode. The effect of the high-order DBR groove shape on the diffraction efficiency of high diffraction orders—parasitic output optical losses—has been experimentally studied. It is shown that the design of a laser resonator with a low reflective output short DBR can significantly reduce the parasitic losses and increase the laser efficiency while maintaining spectrally selective features over the entire range of pump currents. It was shown that pulse pumping (2–100 ns) does not impair the spectral selectivity of the high-order DBR and ensures a laser line width of 0.3 nm even in the range of high pump levels (50 A/1 00 ns). Investigations of a pulsed 2 ns time-resolved laser pump demonstrated that there is no influence of the electrically passive absorbing section of the DBR on the shape of the optical pulse.